(untitled) (Physical Culture and Sport: Scientific Perspective, 2025)
The requirements of program-normative documents for the training of young football players have contradictions related to the irrational ratio of physical loads, control measures, and the lack of consideration of modern trends. To establish the relationships of physical and technical preparedness indicators of football players in their first year of training at the initial preparation stage. Theoretical analysis and generalization of scientific and methodological literature data, abstraction, historical method, comparison, pedagogical testing, methods of mathematical statistics. Pedagogical testing of physical preparedness (9 tests) and technical preparedness (8 control exercises) was applied to achieve the objective. 73 football players aged 6-7 years at the initial preparation stage, training in sports sections of Ivano-Frankivsk city, were involved. For children aged 6-7 years, training should combine entertainment and learning, emphasizing enjoyment of the process with simple instructions. The analysis of correlation matrices between the indicators of physical and technical preparedness of young football players showed that: only six relationships were recognized as statistically significant; high-density relationships between physical preparedness indicators were not found, which is expected for young athletes; three pairs of medium-density relationships: squats for 10 seconds and long jump (r = 0.487), shuttle run with carrying tennis balls and skipping rope jumps (r = -0.439), shuttle run with carrying tennis balls and 15-meter run (r = 0.488). Regarding technical preparedness, three medium-density relationships were established between the results of comprehensive assessment of ball handling abilities and direction change, ball handling over a 30-meter straight distance, and other similar indicators. The analysis results emphasize the importance of considering the age-specific characteristics and needs of children when forming training programs. In particular, focusing on entertainment and learning through play, as well as adapting training to the specific characteristics of each age group, are key aspects for the effective training of young football players.